THE EFFECT OF TEACHER LANGUAGE STYLE ON STUDENTS’ COMPREHENSION AND MOTIVATION AT SMPN 11 MAKASSAR - Gina Utami; Mutmainnah Mursidin; Jusmaniar Nonci (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2026)
This study explores how teachers’ language styles affect students’ comprehension and motivation in English learning at SMPN 11 Makassar. Adopting a descriptive qualitative design, data were collected through classroom observations across three meetings and semi-structured interviews with the English teacher and selected students. Analysis followed Miles, Huberman, and Saldaña’s interactive model of qualitative data analysis (data reduction, data display, and conclusion drawing). The findings indicate that the teacher employed a combination of four language styles formal, informal, consultative, and expressive switching among them according to classroom context. The expressive style (characterized by varied intonation, humor, gestures, and positive feedback) was the most frequently observed and contributed significantly to students’ engagement, willingness to participate, and comprehension of the material.